Analysis of the Effect of High Opening Variation on the Performance of Castellated Beams using the Reduced Beam Section Method - Aswad, Nini H.; Pongsimpin, Dendi; Azikin, Thahir; Rachman, Ranno Marlany; Tachrir, .; Tumpu, Miswar (Engineering, Technology & Applied Science Research, 2025)
Castellated beams are widely used in structural applications due to their improved load-bearing capacity and material efficiency. This study examines the effect of the variations in the opening height of castellated beams using the Reduced Beam Section (RBS) method, aiming to determine the optimal opening height based on tension, strain, deflection, and stiffness. The modeling results show that increasing the opening height leads to higher stress and strain in the beam. Modeling with an opening height of 190 mm resulted in the highest tension of 311.03 MPa and strain of 0.016, while an opening height of 110 mm recorded a stress of 269.41 MPa and a strain of 0.003. The lowest deflection of 9.87 mm and the highest stiffness of 8.22 kN/mm were obtained at an opening height of 150 mm, rendering it the optimal opening height. It is concluded that this opening height provides the most efficient balance between tension, strain, deflection, and stiffness in castellated beams with RBS. Further research is proposed to analyze the fatigue behavior and long-term performance of the castellated beams with different opening configurations under dynamic loading conditions.